Overutilization of Cross-Sectional Imaging in the Lower Extremity Trauma Setting - Protack, Clinton; Wengerter, Brian; Jean, Raymond A.; Liu, Shirley; Mojibian, Hamid; Sumpio, Bauer; Dardik, Alan; Maung, Adrian A.; Erben, Young (International Journal of Angiology, 2018)
Objective In an era of managed care and cost savings, we are faced with the question of whether another test is necessary to confirm our clinical suspicion. We hypothesized that a few computed tomography angiographies (CTAs) are necessary to identify lower extremity vascular injuries (LEVIs). We reviewed our trauma center's experience in the management of LEVI.Methods A retrospective review of all trauma patients between 2012 and 2016 was performed. Four-thousand nine-hundred fourteen trauma patients were evaluated with 46 suspected LEVIs (either with cross-sectional imaging and/or operative exploration). Our primary end point was the utility of CTA in the setting of LEVI. Receiver operating characteristic curves were performed to evaluate sensitivity and specificity for hard signs and CTA identification of LEVI.Results Out of the initial 46 patients with suspected LEVI, 41 (89%) had a CTA as part of their initial evaluation. Sixteen patients (35%) with LEVI were due to penetrating injuries. Seventeen patients (41%) had a CTA with LEVI. Fourteen of the 17 patients (82%) with injury on CTA also had hard signs of LEVI. Twenty-two patients (48%) underwent operative exploration: three had no LEVI that was previously believed to be on CTA; operative exploration identified two missed injuries not observed on CTA. Seven of forty-one (17%) CTA studies provided a false assumption of the presence/absence of LEVI. One patient (2%) underwent operative exploration and was found to have LEVI in the absence of hard signs, but with a CTA identifying LEVI.Conclusion The recognition of hard signs through physical examination is paramount to assessing need for operative intervention with suspicion of LEVI. CTA should be reserved as an adjunct for identification of LEVI in patients with high clinical suspicion and absence of hard signs, rather than utilizing CTA as an initial screening tool for the identification of LEVI.
Keywords: trauma; lower extremity; artery; ultrasound; repair; femoral artery; ankle-brachial index